(untitled) (Research, Society and Development, 2021)
Teachers’ conceptions are presented as organizers of an innovative teacher training course, the Degree Course in Natural Sciences: Chemistry and Biology, offered by the Federal Institute of Science and Technology - Campus Porto Alegre, in response to national demand of teachers in the area of Natural Sciences. For the construction of the analysis corpus, the transcripts of the interviews carried out with teachers who created and developed the course were used, using the Discursive Text Analysis as the analysis methodology. Still, in the referred article, it is possible to know the course’s curricular structure through the analysis of excerpts from the Political Pedagogical Project of the Course. Through the analysis of the interviews it was possible to know the stages that culminated with the construction of the course, its mishaps and successes, in addition to allowing to know the persistence and dedication of the teachers in creating a course with a unique identity, capable of forming graduates prepared to supply to shortages by teachers engaged in the teaching profession.